Relevance of Traditional Islamic Education in Indonesia in the Era of Globalization: Challenges and Adaptation Strategies: صلة التعليم الإسلامي التقليدي بإندونيسيا في عصر العولمة: دراسة مكتبية حول التحديات واستراتيجيات التكيف - Mahfuz Abdul Rajak; Niswatun Kholifah; Mohamed El Mustafa Abdel Gabar (Civilization Research: Journal of Islamic Studies, 2026)
Through rapid technological advancement, social change, and increasing global competency demands, globalization has significantly transformed educational systems. These developments require traditional Islamic education to preserve its Islamic values and adapt to contemporary challenges. This study examines the relevance of traditional Islamic education in the era of globalization, identifies its major challenges, and creates appropriate adaptation strategies. A qualitative library research approach was employed by analyzing scholarly books, journal articles, and other relevant academic sources. The findings indicate that traditional Islamic education remains highly relevant in fostering moral character, spirituality, and religious moderation. However, it faces challenges related to digital transformation, cultural shifts, and competition with modern educational institutions. Adaptation strategies include integrating educational technology, reforming the curriculum, strengthening teachers’ competencies, enhancing character education, and promoting collaboration with universities, governments, and digital institutions. This study’s novelty lies in proposing a conceptual adaptation model that integrates the preservation of traditional Islamic educational values with the demands of global educational transformation. The findings provide policy recommendations for developing adaptive, innovative, and sustainable Islamic education systems.